A 10‐year review of surgical management of dermatofibrosarcoma protuberans. (16th September 2020) - Durack, A.; Gran, S.; Gardiner, M.D.; Jain, A.; Craythorne, E.; Proby, C.M.; Marsden, J.; Harwood, C.A.; Matin, R.N.; ,
Summary: Background: Dermatofibrosarcoma protuberans (DFSP) is a rare skin cancer. Standard treatment in the UK is either wide local excision (WLE) or Mohs micrographic surgery (MMS). It is unclear which approach has the lower recurrence rate. Objectives: We undertook a retrospective comparative review of surgical management of DFSP in the UK National Health Service in order to define (i) current surgical practice for primary and recurrent DFSP, (ii) local recurrence rates for primary DFSP and (iii) survival outcomes for DFSP. Methods: A retrospective clinical case‐note review of patients with histologically confirmed DFSP (January 2004 to December 2013) who have undergone surgical treatment. Results: The surgical management of 483 primary and 64 recurrent DFSP in 11 plastic surgery and 15 dermatology departments was analysed. Almost 75% of primary DFSP ( n = 362) were treated with WLE and 20% ( n = 97) with MMS. For recurrent DFSP, 69% ( n = 44) and 23% ( n = 15) of patients underwent WLE and MMS, respectively. Recurrent primary DFSP occurred in six patients after WLE and none after MMS. The median follow‐up time was 25·5 months (interquartile range 6·8–45·1) for new and 19·8 (IQR 4·5–44·5) for recurrent DFSP [Correction added on 1 Feb 2021, after first online publication: 4.8 years (interquartile range 3.5‐5.8) was incorrect], with eight reported deaths during the follow‐up analysis period (one confirmed to be DFSP related). Conclusions: WLE was the most common surgical modality used to treat DFSP across the UK. The local recurrence rate was very low, occurring only after WLE. Although a prospective randomized controlled trial may provide more definitive outcomes, in the absence of a clearly superior surgical modality, treatment decisions should be based on patient preference, clinical expertise and cost. Abstract : What is already known about this topic? Surgical management of dermatofibrosarcoma protuberans (DFSP) includes wide local excision (WLE) with or without margin control. Although Mohs micrographic surgery (MMS) or similar margin‐controlled excision is advocated in the UK, this appears to be based on consensus guidance and low‐quality data, with few centres routinely providing this expertise. What does this study add? This is the largest case series of DFSP reported from the UK to date, with three‐quarters of the 483 primary DFSP treated between 2004 and 2014 being managed with WLE. Six local recurrences were found in the WLE group and none in the MMS group. In individuals with primary DFSP who underwent WLE, complete histological clearance occurred less frequently at the first attempt (81·4%) than in those who were treated with MMS (87%). Linked Comment: van denBos. Br J Dermatol 2021; 184 :595 .